1979
DOI: 10.3109/00365597909181172
|View full text |Cite
|
Sign up to set email alerts
|

Uraemic Arterial Disease

Abstract: A histophatologic study of uraemic arterial lesions was performed in rats. They were made uraemic by 5/6 kidney resection, and the aorta and peripheral arteries were examined after intervals of up to 36 weeks. The characteristics of the arterial lesions were necrosis of medial smooth muscle cells and, in some cases, calcification of the media. The changes appeared first in the aorta, but after long uraemic periods also in peripheral arteries. The incidence and severity of necrosis and of calcification were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…In the human situation, arterial calcifica tions arc frequently observed in chronic renal failure [84,85] similarly to what has been described in uremic rats [82], This anomaly could be in part attributed to a disturbed Caphosphate metabolism. However, it has been reported that the arterial lesions consist of calcified structures encountered in areas of the arterial walls with severe degenerative alterations (i.e., cell damage), not of diffuse calcifications of the ground substance [86], These lesions were not associated with the accumulation of lipids and differed thus from those observed in common atherosclerosis.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…In the human situation, arterial calcifica tions arc frequently observed in chronic renal failure [84,85] similarly to what has been described in uremic rats [82], This anomaly could be in part attributed to a disturbed Caphosphate metabolism. However, it has been reported that the arterial lesions consist of calcified structures encountered in areas of the arterial walls with severe degenerative alterations (i.e., cell damage), not of diffuse calcifications of the ground substance [86], These lesions were not associated with the accumulation of lipids and differed thus from those observed in common atherosclerosis.…”
supporting
confidence: 55%
“…Similarly, short-term uremia in rats was not associated with mor phological changes, despite significant hyper-lipidcmia, which did nol lead to an increased aortic lipid content or accentuate early histo logical lesions of atherosclerosis [81]. In con trast, long-term uremia in rats induced signif icant arterial changes [82], In personal stud ies, we have expressed the occurrence and severity of lipid deposits within caudal ar terial lesions of chronically uremic rats (5 weeks) in terms of a score which takes into account the percent incidence of fatty lesions per total number of lesions as well as the intensity of the specific coloration for lipids within each fatty lesion [83]. We have found a strong positive relationship between the score of caudal artery lesions and total serum chol concentration as well as serum creati nine level.…”
mentioning
confidence: 93%
“…Coronary artery plaques in patients with ESRD are more calcified than those in age-and gender-matched patients with coronary artery disease and normal kidney function (34). In addition, calcifications of the arterial wall medial layer are frequently observed in arterial specimens obtained from uremic patients (7,11), rats (35), and rabbits (36). It has been suggested that the arterial wall calcifications are caused by the changes in the calcium/phosphate metabolism that accompanies uremia (7,37).…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark of all these studies is the development of uremia and CKD-related complications similar to the human condition. To the best of our knowledge, the first report of vascular calcification, using the 5/6Nx model, was published in 1979 [13]. Subsequently, the first mouse model of CKD reported by Gagnon and Duguid [14] in 1983 used a slightly different approach that continues to be employed by several groups to study vascular calcification outcomes.…”
Section: Animal Ckd Models Develop Vascular Calcificationmentioning
confidence: 99%
“…Ejerblad et al [13], using 5/6Nx in Sprague-Dawley (SD) rats, were the first to report aortic calcification after 12–36 weeks using a 1% by weight phosphorus-containing diet (table 1). Interestingly, the data suggest that without a high phosphorus diet the commonly used SD rat strain was resistant to vascular calcification.…”
Section: The 5/6 Nephrectomy Model Of Ckdmentioning
confidence: 99%